New approaches to control and detect enterotoxic Staphylococcus aureus strains - Baptista, Maria Inês Ramos Pilreira (2018)
With 25 million cases of foodborne diseases occurring annually worldwide, food safety is a major concern. Despite considerable efforts to improve food safety, outbreaks of foodborne diseases due to the presence of pathogenic microorganisms, such as Staphylococcus aureus, are well described in the literature. S. aureus is a well-adapted opportunistic pathogen, which is able to grow in numerous types of food, producing an extensive number virulence factors, including enterotoxins, which are responsible for staphylococcal food poisoning. This type of food poisoning is one of the most prevalent foodborne diseases in the world. With an increased demand for safer food, new food preservation technologies have been developed. Among these technologies is high pressure processing (HPP), which is a non-thermal food preservation method that enables the inactivation or control of pathogenic microorganisms and microorganisms responsible for food spoilage, maintaining food properties. The quick and specific detection of pathogenic microorganisms (or of microorganisms responsible for food spoilage) has become increasingly important in the food industry. Usually the detection, and identification of bacteria is performed using traditional methods based on biochemical and/or serological tests and also on molecular methods based on DNA or RNA analysis. However, these methods are costly, time consuming and laborious. Consequently, it is necessary to develop new alternative methods, such as those based on microbial metabolomics, which can be used as a tool to detect microorganisms in the food industry. Microbial metabolomics uses the metabolites released by microorganisms, being able to allow not only the detection and distinction of microbial species, but also the distinction of their strains. One of the objectives of this work was to evaluate the efficacy of HPP treatment for the inactivation of non-enterotoxic and enterotoxic S. aureus strains. Thus, to accomplish this objective, 1) the effectiveness of different treatments (different pressures and holding times were evaluated); 2) the impact of the treatments on virulence factors, fermentation of mannitol and methicillin susceptibility was evaluated; 3) the development of resistance along several successive HPP cycles was evaluated, and 4) the recovery capacity after 14 days of treatment was also assessed. Other objective of this study was to characterize the volatile exometabolome of S. aureus and evaluate its potential to distinguish the enterotoxic strains from the non-enterotoxic strain. For this purpose, 1) the profile of the volatile exometabolome of S. aureus was characterized using an advanced gas chromatography technique; 2) the S. aureus profile was analyzed as a whole and evaluated the presence of specific compounds already described for this species as well as its metabolic origin; 3) a multivariate statistical analysis method was applied in order to obtain a set of volatile compounds responsible for the distinction of the three strains used; and 4) these set of volatile compounds were analyzed in detail in order to explain the differences between strains, thus justifying their separation. The results of inactivation by HPP showed a higher barotolerance of the non-enterotoxic strain (ATCC 6538), not being completely inactivated at 600 MPa for 30 minutes (maintaining a viability of approximately 4 Log CFU.mL-1). The two enterotoxic strains (2153 MA and 2065 MA) were completely inactivated using these treatment conditions. Both strains ATCC 6538 and 2153 MA (with an enterotoxin) were able to withstand 10 successive pressurization cycles, whereas the strain 2065 MA (with three enterotoxins) was completely inactivated after 4 cycles, with a decrease of 9.2 log CFU.mL-1. The HPP treatment did not affect none of the tested virulence factors, the mannitol fermentation ability and methicillin susceptibility of any of the strains. Moreover, none of the strains were able to recover their viability after 14 days of incubation in any of the treatment cycles. The study of the volatile exometabolome of S. aureus allowed the detection of 240 volatile organic compounds, belonging to 10 chemical families, having as main metabolic origins the degradation of amino acids, the metabolism of pyruvate and oxidative stress. It was also possible to find 10 of the most reported volatile compounds in studies concerning the volatile exometabolome of S. aureus. The detailed analysis of the volatile exometabolome allowed selecting 10 volatile compounds that have been reported more frequently in other studies concerning the volatile exometaboloma of S. aureus. The multivariate statistical analysis, allowed to distinguish the strains based on the number (or absence) of enterotoxins. The strains ATCC 6538 and 2153 MA are more similar to each other, being separated from the strain 2065 MA. This distinction is due to the latter strain has larger amounts of volatile compounds, resulting from the degradation of branched-chain amino acids, while the strain ATCC 6538 showed higher amounts of volatile compounds with origin in the degradation of methionine. In conclusion, the results showed that HPP is effective in the control of S. aureus, not allowing the development of resistance or recovery of viability after successive treatments. Although the virulence factors were not affected by HPP treatment, the enterotoxic strains were more easily inactivated than the non-enterotoxic strain. It was also concluded that the volatile exometabolome of S. aureus is quite complex and that the exometabolome analysis allows to distinguish enterotoxic strains from non-enterotoxic strains. It was possible to select a set of 10 compounds that can be potentially used as biomarkers of S. aureus.